Pelatihan corel draw untuk pengembangan soft skill siswa SMKN 2 Kota Madiun - Ubaidillah, Moh.; Widiasmara, Anny; Sudrajat, Muhamad Agus (Nur Science Institute, 2023)
Graphic design is a form of communication that utilizes an image to convey a message. Graphic design can convey messages easily understood. One form of graphic design products is logos and posters. The purpose of implementing this community service activity is to provide knowledge to SMKN 2 Madiun City students about introducing the basic principles of design and color psychology theory and provide training on making poster logo designs using Corel-Draw. The participants in this training were 35 students. The method of implementing this community service goes through five stages: 1) problem formulation, 2) determination of solutions, 3) completion method, 4) evaluation, and 5) output. Based on the results of the implementation of community service activities, the pre-test lowest score is 40, the highest score is 70, and the lowest score is 65 in the post-test. The highest score is 90, so participants have increased knowledge and ability to do poster design after attending this training.